Describing an Excellent University Instructor: Towards Developing a New Paradigm - Aclao, Joel T.; Abasolo, Aida G.; Villacora, Marc Will L.; Manego, Chrissa Faith M. (JPAIR Multidisciplinary Research, 2014)
Universities and colleges use different constructs in describing excellent instructor. The study aimed to analyze students’ descriptions of excellent instructors, to report the descriptions as themes, and to develop a new paradigm of an excellent university instructor. The researchers reviewed comments from the 836 Learning Environment Survey results completed by the students coming from the 44 classes of the subject instructors. A total of 22 excellent instructors coming from the different colleges composed the subjects of the study. This qualitative study used thematic analysis to report the emergent themes. The study revealed that students describe excellent university instructors as content expert, facilitator, motivator, and role model. As an output, the study develops a new paradigm of excellent university instructor. However, the constructs of the paradigm need further study for validation.